MENGUKUR DAMPAK PENDEKATAN STEAM TERHADAP LITERASI SAINS: SEBUAH STUDI META-ANALISIS - Haliza, Natasya Wanda; Bidayati Haka, Nukhbatul; Oktina Sari Pratama, Anisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine how much influence the STEAM approach has on overall scientific literacy based on educational level, region and also learning materias. This study uses a meta-analysis research design and is quantitative in nature. With the help of Publish or Perish, which is indexed by SINTA, data was gathered using the PRISMA rules, which were obtained via Google Scholar, during the February 2021–2025 time frame. Nine articles that satisfied the predetermined criteria were identified from the 636 articles in the initial data set. JASP-0.19.3.0 software helped with the study's data analysis. The study's findings demonstrated that the STEAM approach significantly improved students' overall scientific literacy (effect size of 0.580, including the moderate category), as well as their learning materials (effect size of 0.580, including the moderate category), educational level (effect size of 0.575, including the moderate category), and region (effect size of 0.585, including the moderate category). Overall, it can be said that students' scientific literacy skills are significantly improved by the STEAM approach.